Approach to the characteristics and postpartum depression in postpartum women from the Peruvian highlands - Lipa-Tudela, Frida (Revista Acciones Médicas, 2024)
Pregnancy, childbirth, and the postpartum period are crucial moments that deeply impact family dynamics, encompassing fundamental aspects from a biopsychosocial perspective. The purpose of this study was to analyze how biological, psychological, and social characteristics are related to postpartum depression in women from the Peruvian highlands. A quantitative methodology with a cross-sectional and descriptive design was employed. The study population consisted of 179 postpartum women from the José Antonio Encinas Health Facility in Puno, Peru, of which 78 participated. Interviews were conducted as the data collection technique, utilizing interview guidelines and the Edinburgh Postnatal Depression Scale. The results revealed that 53% of postpartum women experienced depression. Regarding biological characteristics, it was observed that those with more than six prenatal check-ups, without obstetric psychoprophylaxis sessions, eutocic births, a history of pregnancy-related pathologies, and no history of pathologies in the newborn, had a higher propensity for postpartum depression. Regarding psychological characteristics, family and partner support were associated with a lower incidence of depression. From a social perspective, women between 25 and 29 years old, with non-university higher education, cohabiting, homemakers, and first-time mothers with only one child showed a higher prevalence of postpartum depression. In conclusion, the importance of prenatal care, partner support, and consideration of age in the timely diagnosis and treatment of postpartum depression are highlighted.
Keywords: biological feature; postpartum depression; psychological; social